Electrostatic Interactions Drive the Self-Assembly and the Transcription Activity of the Pseudomonas Phage ϕ6 Procapsid - Sun, Xiaoyu (American Society for Microbiology, 2014)
Assembly of an empty procapsid is a crucial step in the formation of many complex viruses. Here, we used the self-assembly system of the double-stranded RNA bacteriophage ϕ6 to study the role of electrostatic interactions in a scaffolding-independent procapsid assembly pathway. We demonstrate that ϕ6 procapsid assembly is sensitive to salt at both the nucleation and postnucleation steps. Furthermore, we observed that the salt sensitivity of ϕ6 procapsid-directed transcription is reversible.